Peningkatan Hasil Belajar Peserta Didik Melalui Model Pembelajaran Problem Based Learning Di SMA N 1 Metro Lampung Tahun Pelajaran 2022/2023 - Bayu Prafitri; Maylisa Isnaini Hidayah (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2023)
This study aims to improve critical thinking skills and learning outcomes of class X senior high school students at SMA N 1 Metro through the application of the Problem-Based Learning (PBL) model. This research is a classroom action research. The research subjects were class X students. Data collection used the observation method with test instruments, observations. The data obtained were analyzed descriptively using data reduction, data presentation, and conclusions. The results of the study show the following: From the test results, most of the students' learning outcomes have increased. It can also be seen that the comparison of values ​​between the pretest and posttest learning outcomes in cycle III has increased where the average pretest result of 73.33 increases in the posttest increased to 88.58. For the results of cycle III, an average value of 88.58 is obtained with the achievement of completeness 96% exceeded the targeted target of completion of 85%. So that through the project-based learning learning model, student learning outcomes have increased by 96%. It can be concluded that the application of learning using the Problem Based Learning Learning Model in Islamic Religious Education Subjects Class X SMA N 1 Metro Lampung can improve Learning Outcomes